Control of Innate and Adaptive Immune Responses during Infectious Diseases - Aliberti, Julio; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
The interface between host and pathogen cells involves a complex series of molecular mechanisms. On one side host cells recognize pathogen structures and initiate immune responses. On the other side, pathogens continually evolve immune escape strategies aiming at establishing chronic disease and transmission to a new host. The balance between those two forces can determine the fate of infectious diseases. Either uncontrolled pathogen replication or tissue damage due to unleashed pro-inflammatory responses can be detrimental to the host. Here we explore immune regulatory mechanisms that take place during some of the most relevant infectious diseases worldwide. We provide a wide spectrum view of the current understanding of how the immune system modulates ongoing responses to prevent host pathology, as well as some immune evasion strategies used by some of those microbes.
Resolution of inflammation during Toxoplasma gondii infection -- Mechanisms of host protection and pathogen evasion of immune response during tuberculosis -- NKT cell activation during (microbial) infection -- Regulation of innate immunity during Trypanosoma cruzi infection -- B cell-mediated regulation of immunity during Leishmania infection -- Control of the Host Response to Histoplasma capsulatum -- Modulation of T-cell mediated immunity by cytomegalovirus -- T cell responses during Human Immunodeficiency Virus (HIV)-1 infection.
Keywords: Medicine; Immunology; Emerging infectious diseases; Microbiology; Biomedicine; Immunology; Microbiology; Infectious Diseases